Experiments on Optimal Vibration Control of a Flexible Beam Containing Piezoelectric Sensors and Actuators - Gustavo L.C.M. Abreu; José F. Ribeiro; Valder Steffen Jr (Shock and Vibration)
In this paper, a digital regulator is designed and experimentally implemented for a flexible beam type structure containing piezoelectric sensors and actuators by using optimal control design techniques. The controller consists of a linear quadratic regulator with a state estimator, namely a Kalman observer. The structure is a cantilever beam containing a set of sensor/actuator PVDF/PZT ceramic piezoelectric patches bonded to the beam surface at the optimal location obtained for the first three vibration modes. The equations of motion of the beam are developed by using the assumed modes technique for flexible structures in infinite-dimensional models. This paper uses a method of minimizing the effect of the removed higher order modes on the low frequency dynamics of the truncated model by adding a zero frequency term to the low order model of the system. A measure of the controllability and observability of the system based on the modal cost function for flexible structures containing piezoelectric elements (intelligent structures) is used. The observability and controllability measures are determined especially to guide the placement of sensors and actuators, respectively. The experimental and numerical transfer functions are adjusted by using an optimization procedure. Experimental results illustrate the optimal control design of a cantilever beam structure.